Moral clarity decreases as viewer age increases: a content analysis of the moral values and reinforcement cues depicted in popular U.S. children's television. Issue 2 (3rd April 2022) - Hahn, Lindsay
ABSTRACT: Evidence suggests that exposure to narrative media content emphasizing the importance of moral intuitions can increase the extent to which children value those intuitions. This is especially the case when intuition exemplars are accompanied by clear social desirability cues (i.e., moral acts are rewarded/performed by heroes or immoral acts are punished/performed by villains). Less is known about the effects of exposure to ambiguous social desirability cues (i.e., moral acts are punished/performed by villains or immoral acts are rewarded/performed by heroes). In order to investigate the extent to which popular media content may serve as an effective moral educator for young viewers, this paper describes a content analysis designed to examine the frequency and clarity of moral intuition exemplars in popular children's television shows (N = 30). Results demonstrated that moral clarity in content decreased as viewer age increased. That is, content popular among older children (ages 6–17) featured more ambiguous social desirability cues compared to content popular among younger children (ages 2–5). Content across age groups also featured a preponderance of care and fairness intuition exemplars. Findings are interpreted in line with extant research on moral complexity and narrative entertainment. Practical implications are considered. IMPACT SUMMARY a. Prior State of Knowledge Recent work has demonstrated that narrative media's emphasis on moral intuitions can increase the importance audiences place on those intuitions. This work largely focuses on understanding the effects of moral exemplars that are clearly reinforced in narratives. b. Novel Contributions Using content analysis, the present study demonstrated that the clarity of narrative reinforcement cues decreases as the age group in which the content is popular increases. Specifically, moral exemplars in television shows popular among teens featured the most ambiguous reinforcement cues. c. Practical Implications For caregivers hoping to use media as a tool for inculcating certain moral values in children, these results suggest the importance of considering not only which moral values are exemplified in content, but also how clearly those values are reinforced.